ANALISIS STRATEGI PEMASARAN RENDANG GADIH MELALUI PLATFORM SHOPEE UNTUK MENINGKATKAN PENJUALAN - Ikka Ade Sophia; Roni Afrizal; Alfikri Alfikri (JURNAL LENTERA BISNIS, 2025)
Rendang Gadih implements digital marketing and is able to increase sales through the shopee platform. The purpose of this research is to analyze the marketing strategy implemented by Rendang Gadih. This research uses a descriptive qualitative approach with data collection methods in the form of interviews, observation, and documentation. The data analysis technique uses the interactive data analysis technique of the Miles and Huberman model (2014): Data reduction, Data presentation and Conclusion drawing. The strategy analyzed refers to the concept STP (Segmentation, Targeting and Positiong) and the 4P marketing mix (Product, Price, Place, Promotion). The results showed that Rendang Gadih applies demographic, geographic, and psychographic segmentation and focuses the target market on consumers outside West Sumatra through digital marketing. Product positioning is strengthened through branding supported by government awards and customer loyalty. The marketing mix strategy is actively implemented through the presence of product variants, the application of psychological pricing and price bundling, the utilization of Shopee CRM and promotions through Shopee Live, Shopee Ads, and Shopee Campaigns. The implementation of this strategy is proven to have a positive impact on sales. This research is expected to be a reference for other UMKM  in optimizing digital marketing to increase competitiveness